Learners' Errors and their Evaluation - Maharjan, Laxmi Bahadur (Journal of NELTA, 2010)
This study identifies, describes and evaluates the learners' errors, and determines the gravity of those errors in terms of intelligibility and acceptability by the Nepali, non-Nepali and native English speaking teachers. This study was targeted at the grammatical errors and perceptions of different English teachers on those errors. The research findings were analyzed and expressed quantitatively. The study revealed that the Nepali English teacher evaluators were found to be the most severe judges. The non- Nepali (i.e. other than Nepali and the native English) evaluators were in between the Nepali and the native English evaluators. The researcher proposes to treat the most serious errors for Nepali and non- Nepali English teachers with priority. Key words: error analysis, grammatical errors, error gravity DOI: 10.3126/nelta.v14i1.3093 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 71-81